Study on the Ultrahigh Quantum Yield of Fluorescent P, O‐g‐C3N4 Nanodots and its Application in Cell Imaging. Issue 27 (1st June 2016) - Rong, Mingcong; Cai, Zhixiong; Xie, Lei; Lin, Chunshui; Song, Xinhong; Luo, Feng; Wang, Yiru; Chen, Xi
Abstract: Graphitic carbon nitride nanodots (g‐C3 N4 nanodots), as a new kind of heavy‐metal‐free quantum dots, have attracted considerable attention because of their unique physical and chemical properties. Although various methods to obtain g‐C3 N4 nanodots have been reported, it is still a challenge to synthesize g‐C3 N4 nanodots with ultrahigh fluorescence quantum yield (QY). In this study, highly fluorescent phosphorus/oxygen‐doped graphitic carbon nitride (P, O‐g‐C3 N4 ) nanodots were prepared by chemical oxidation and hydrothermal etching of bulk P‐g‐C3 N4 derived from the pyrolysis of phytic acid and melamine. The as‐prepared P, O‐g‐C3 N4 nanodots showed strong blue fluorescence and a relatively high QY of up to 90.2 %, which can be ascribed to intrinsic phosphorus/oxygen‐containing groups, and surface‐oxidation‐related fluorescence enhancement. In addition, the P, O‐g‐C3 N4 nanodots were explored for cell imaging with excellent stability and biocompatibility, which suggest that they have great potential in biological applications. Abstract : Nanodot doping : An efficient method was developed to synthesize highly fluorescent phosphorus/oxygen‐doped graphitic carbon nitride (P, O‐g‐C3 N4 ) nanodots (see scheme). A study on the effect of synthetic parameters on the QY revealed that the size and surface functional groups of the P, O‐g‐C3 N4 nanodots influence the QY, and could be regulated by means of the raw materials ratio, the hydrothermal etching temperature, and the reaction time.